Pelatihan Akuntansi Bank Transaksi Back Office Bank Konvensional Bagi SMK Unitomo Surabaya - Evi Sistriyarini; Herizon; Carolyn Lukita Sembiring (Universitas Lancang Kuning, 2020)
Senior Vocational School of Unitomo Surabaya is one of scholl in Surabaya that have cooperated with STIE Perbanas Surabaya. One of majoring in Senior Vocational School of Unitomo Surabaya is accounting. There are two problems faced Senior Vocational School of Unitomo Surabaya. They are the limited learning of banking accounting and the accounting learning process is still done manually. This community service activity is carried out by providing banking accounting training of back office transaction in Conventional Bank for Senior Vocational School of Unitomo Surabaya. This activity provides additional knowledfe for teachers and students of Senior Vocational School of Unitomo Surabaya about back office transaction in Conventional Bank both in theory or practice.